2014
DOI: 10.4103/0973-029x.151360
|View full text |Cite
|
Sign up to set email alerts
|

Myoepithelial cell carcinoma of the oral cavity: A case report and review of literature

Abstract: Myoepithelial carcinoma (MC) is a malignant salivary gland neoplasm whose tumor cells demonstrate cytologic differentiation toward myoepithelial cells and lack ductal or acinar differentiation. It is a relatively rare tumor and many a times remains undiagnosed because of histopathological heterogeneity. It represents about 0.4–0.6% of all salivary gland tumors and 1.2–1.5% of carcinomas. It occurs predominantly in the parotid gland with a mean age of presentation being 55 years (range 14–86) with no sex predil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The efficacy of radiotherapy and chemotherapy is still controversial. [20][21][22][23] In the present study, no correlation was noted between a better prognosis and the use of postoperative radiotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 84%
“…The efficacy of radiotherapy and chemotherapy is still controversial. [20][21][22][23] In the present study, no correlation was noted between a better prognosis and the use of postoperative radiotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 84%
“…Morphologic heterogeneity of tumor cells in MC include epithelioid, plasmacytoid, spindle, clear, stellate and mixed type. [ 5 ] Kane et al . in a series of 51 cases of MC, observed that minor gland involvement (almost 75%) exceeded major salivary gland involvement (<25%).…”
Section: Discussionmentioning
confidence: 99%
“…The ulceration proves a more aggressive variant histopathologically that is spindle cell variant. [ 5 ] Histopathologically, predominantly clear cells were present along with epithelioid cells in a hyalinized scant stroma. Benign and MMs may pose a dilemma in diagnosing as the features, and cellular type may be common.…”
Section: Discussionmentioning
confidence: 99%
“…Myoepithelioma and its malignant counterpart, myoepithelial carcinoma, of the salivary glands are neoplasms made up almost exclusively of tumour cells with myoepithelial differentiation [ 6 ]. Their differential diagnosis includes a wide range of both benign and malignant tumours, depending on the predominant cell type: epithelioid, spindle, hyaline, clear cell [ 8 ]. In particular, the main differential diagnosis of myoepithelioma is pleomorphic adenoma (PA) [ 3 , 9 ].…”
Section: Discussionmentioning
confidence: 99%